2011
DOI: 10.1111/j.1467-7687.2011.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

Refining the understanding of inhibitory processes: how response prepotency is created and overcome

Abstract: Understanding (a) how responses become prepotent provides insights into when inhibition is needed in everyday life. Understanding (b) how response prepotency is overcome provides insights for helping children develop strategies for overcoming such tendencies. Concerning (a), on tasks such as the day-night Stroop-like task, is the difficulty with inhibiting saying the name of the stimulus due to the name being semantically related to the correct response or to its being a valid response on the task (i.e. a memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
86
0
12

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 42 publications
6
86
0
12
Order By: Relevance
“…Taking a short delay generally leads to fading of the load of the impulsive response, which then becomes replaced by a more self-regulated response. This Passive Dissipation Model (Simpson et al, 2012) has been shown by many studies. Diamond, Kirkham, and Amso (2002), for example, compared six conditions to reduce inhibitory and/or memory load in an EF-task and showed that young children's performance increased most when they were provided with short delays between stimulus and response.…”
Section: Helping Children To Support Their Efs Through Embedded Exercmentioning
confidence: 88%
See 2 more Smart Citations
“…Taking a short delay generally leads to fading of the load of the impulsive response, which then becomes replaced by a more self-regulated response. This Passive Dissipation Model (Simpson et al, 2012) has been shown by many studies. Diamond, Kirkham, and Amso (2002), for example, compared six conditions to reduce inhibitory and/or memory load in an EF-task and showed that young children's performance increased most when they were provided with short delays between stimulus and response.…”
Section: Helping Children To Support Their Efs Through Embedded Exercmentioning
confidence: 88%
“…Two interlinked activities that have shown effective are inserting short delays and verbal self-monitoring (Fradley, 2005;Bodrova & Leong, 2007;Fernyhough & Fuhs & Day, 2011;Simpson et al, 2012). Through verbal self-monitoring, children are elicited longer response latencies to reduce the load on their first prepotent impulse and to formulate more self-regulated responses (Simpson et al, 2012;Diamond, 2013). Moreover, repeated practice with such EFactivities may lead to internalization over time with stronger benefits on the long-term as well (Holmes et al, 2009;Fuhs & Day, 2011;).…”
Section: Helping Children To Support Their Efs Through Embedded Exercmentioning
confidence: 94%
See 1 more Smart Citation
“…The stimuli were linguistic and had a semantic relation between the to-be-inhibited and correct responses (i.e., "dog" and "cat" are semantically related). Both of the semantic representations were activated and held in an activated state during the task (Simpson et al, 2012). This task required children to inhibit the semantically-related representation in order to correctly respond to the target, which may have been difficult for the PLI group because of their weakness in processing and inhibiting semantically-related information (Cummings & Ceponiene, 2010).…”
Section: Inhibitionmentioning
confidence: 99%
“…This suggests that the primary demand in these tasks is response inhibition (Montgomery & Koeltzow, 2010;Simpson & Riggs, 2005). Second, when a delay is interposed between the presentation of the stimulus and when the child can respond on these tasks, children's performance markedly improves (e.g., Diamond, Kirkham, & Amso, 2002;Jones, Rothbart, & Posner, 2003;Ling, Wong, & Diamond, 2016;Montgomery & Fosco, 2012;Simpson et al, 2012). As noted by Ling et al (2016), preschool children are often so eager to respond that they tend to respond with the first thing that comes to mind, making inhibition particularly challenging.…”
mentioning
confidence: 99%